Harnessing the Global Recovery, A Tough Road Ahead - World Bank (Washington, DC, 2014)
Many countries in Middle East and North Africa (MENA) will start to benefit from stronger external demand in the high-income economies, as the global economy is set for a rebound in 2014. After a marked slowdown in 2013, a recovery in high income economies is expected to boost global growth to 3.2 percent in 2014, an increase by 0.8 percentage points compared to 2013. Global output is expected to improve further in 2015 with real gross domestic product (GDP) accelerating to 3.4 percent in 2015. The World Bank estimates that growth in the United States (U.S.) will increase by 1 percentage point reaching 2.8 percent in 2014 and 2.9 percent in 2015; and the Euro Zone will improve to 1.1 percent and accelerate to 1.4 percent in 2014 and 2015 respectively, relative to negative 0.4 percent growth in 2013. The growth rebound in the Euro Zone is largely export led, with Germany and France continuing to expand at a solid pace, and Spain exiting recession. The world travel and tourism council estimates show that tourism revenues will increase by 7 percent in the MENA region in 2015 relative to 2014. To be sure, the global recovery is still fragile and downside risks, including continued low inflation in high-income economies, which can weaken demand and delay the economic recovery, and the escalation of conflict in Ukraine remain. This report presents the short-term, regional macroeconomic outlook, and economic challenges facing the countries in the MENA region. In this report, the MENA region is divided into three subgroups: the Gulf Cooperation Council (GCC) oil exporters, developing oil exporters, and oil importers.